The effect of fluid loss on Olympic distance triathlon performance in high thermoregulatory stress - Coutts, A. J.; Reaburn, P. R. J.; Mummery, W. K.; Abt, G. A.; Humphries, B.; Schofield, G. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
The purpose of this study was to measure the effect of ad-libitum fluid intakes and sweat losses on Olympic distance triathlon (ODT) performance. Ten (3 female and 7 male) trained triathletes ( .V O2max = 58.4 ± 7.7 mL•kg-1•min-1; Best ODT time = 131.5 ± 13.3 minutes) completed two ODT`s (1.5-km swim, 40-km bicycle, 10-km run), two weeks apart. The average wet-bulb globe temperature outdoors (WBGTout) was 28.0 ± 2.8 oC. ODT relative body mass change, sweat loss, sweat rate and fluid intake were found to be 3.86 ± 0.76 %BM, 4370 ± 937 mL, 1886 ± 503 mL•hr-1 and 1551 ± 550 mL, respectively. Run time was significantly influenced by ad-libitum fluid consumption during and the relative body mass change during that leg. Similarly, high sweat rate, high sweat loss but decreased relative body mass losses were all significantly correlated with increased bicycle leg performance. Although swim leg time was significantly related to ODT time, no measures of sweat or fluid intake correlated with swim performance.